Analisis Penerapan Akuntansi Atas Biaya Perbaikan Dump Truck Pada PT. Waletindo Setia Persada - Amelia, Amelia; Azmi, Zul; Rodiah, Siti (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2022)
The application of accounting has an important influence on the financial system of a company. This study aims to determine whether the treatment or application of cost accounting for Dump Truck repairs at PT. Waletindo Setia Persada whether it is in accordance with PSAK 16 or not. The discussion in this study is about how to apply accounting for repair costs at PT. Walentindo Setia Persada in the recognition of accounting acquisitions, as well as measurement and disclosure of the accounting system.This research uses evaluation, analysis and analysis of alternative sharing or techniques with qualitative research types then the data is processed through data reduction which is tested for data wetness. From the results of the research conducted, the researchers obtained the results of the research that the accounting of PT. Walentindo Setia Persada has not complied with accounting principles and has not complied with PSAK 16.